A rare case of double ectopic thyroid in the superior mediastinum: a case report. Issue 2 (22nd February 2023) - Nagireddy, Tejus V; Vaidya, Advait A; Gupta, Samir; Kshirsagar, Pankaj; Kamble, Tushar
Abstract: Primary ectopic mediastinal thyroid is rare, seen in <1% of patients with ectopic thyroid. A patient with two ectopic foci in mediastinum is even rare. Our patient presented with chronic cough and discomfort. CT scan revealed a huge 7 cm × 7 cm (right) and 5 cm × 5 cm (left) mass in mediastinum. IR-guided biopsy of the right side mass showed an ectopic thyroid tissue (ETT). Due to close proximity with major vessels, sternotomy is done and the two masses are excised. The masses were not connected in any way with each other as well as with the orthotopic thyroid in the neck. Pathology revealed colloid goiter. Surgical excision of a mediastinal mass is warranted. This helps in both the diagnosis and potentially be the primary treatment as well. Patients with ectopic thyroid disease are rare, and a presentation of two ETTs on both sides of mediastinum is very rare.